Effects of short-distance transportation on physiological indexes, intestinal morphology, microbial community, and the transcriptome of the jejunum in weaned piglets - Fu, Qin; Yang, Xuesong; Zhou, Sitong; Yang, Yue; Zhang, Xiaohong; Han, Qi; Ji, Wenbo; Liu, Honggui (Frontiers in Veterinary Science, 2023)
Transportation of livestock is unavoidable in animal production. The purpose of this study was to determine the effects of short-distance road transportation lasting 2 hours on the jejunum of weaned piglets. Compared with the control group, there was no impact on the growth performance of piglets in the transport group (P > 0.05). The concentrations of cortisol, heat shock protein (HSP)70, HSP90, C-reactive protein, interleukin (IL)-6, IL-8, IL-12, and interferon-γ, and the activity of reactive oxygen species, were all increased in the jejunum of piglets in the transport group (P < 0.05 compared with the control group). The concentrations of glutathione peroxidase, claudin-1, occludin, and zonula occludens-1 showed no between-group differences (P > 0.05). Regarding intestinal morphology, the transport group showed infiltration of a small amount of lymphocytes into the jejunum mucosa epithelium that was accompanied by edema of the lamina propria, whereas the control group showed no obvious abnormalities. 16S rRNA sequencing revealed, at the genus level, a downward trend in the relative abundance of Lactobacillus and an upward trend in the relative abundance of Muribaculaceae_unclassified in the transport group. There was also increased mRNA expression of genes associated with inflammation in the transport group, but the genes and pathway related to apoptosis were not activated. In summary, weaned piglets undergoing 2 hours of short-distance road transportation showed stress and inflammatory reactions of the jejunum, but did not exhibit oxidative damage or activation of the apoptosis pathway of the jejunum. Furthermore, the growth performance of the piglets was not affected by the trip.